PELATIHAN BUDIDAYA JAMUR TIRAM PUTIH DI YAYASAN AKADEMI PERADABAN DESA DANGAU DATUK KECAMATAN SELEBAR KOTA BENGKULU - Harvela Liana; Agus Zainal Rachmat; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2020)
This research is a descriptive qualitative research which aims to describe the training method for cultivating white oyster mushrooms at the Akademi Per Civilization Foundation, Dangau Datuk Village, District as wide as Bengkulu City which is held in Bukit Makmur Village, North Bengkulu Regency. The research subjects in this study were the Director of the Dangau Village Civilization Academy Foundation, Datuk Village, training instructors, and training participants in white oyster mushroom cultivation. This research was conducted at the Dangau Datuk Village Civilization Academy Foundation and Bukit Makmur Village, North Bengkulu on 16 s.d. March 23, 2020. The data collection techniques used interview, observation and documentation techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation techniques. The results showed that the white oyster mushroom cultivation training methods used by the training instructors for white oyster mushroom cultivation were lecture, question and answer, and demonstration methods. Training on white oyster mushroom cultivation at the Dangau Datuk Village Civilization Academy Foundation was held in a prosperous hill village with more emphasis on demonstration methods. With the demonstrator method, the process of accepting training participants given by the instructor will be more memorable. Keywords: Training, Cultivation, White Oyster Mushroom